Preparation and characterization of activated carbon from palm shell by chemical activation with K2CO3 - Adinata, D.; Daud, Wan Mohd Ashri Wan; Aroua, M.K. (Elsevier, 2007)
Palm shell was used to prepare activated carbon using potassium carbonate (K2CO3) as activating agent. The influence of carbonization temperatures (600-1000 °C) and impregnation ratios (0.5-2.0) of the prepared activated carbon on the pore development and yield were investigated. Results showed that in all cases, increasing the carbonization temperature and impregnation ratio, the yield decreased, while the adsorption of CO2 increased, progressively. Specific surface area of activated carbon was maximum about 1170 m2/g at 800 °C with activation duration of 2 h and at an impregnation ratio of 1.0.